Skatteministeriets kørselsafgifter for lastbiler - Zabic, Martina; Hansen, Per Skrumsager; Clemmesen, Henrik; Meiner, Maria; Kveiborg, Ole; Odgaard, Thomas (Proceedings from the Annual Transport Conference at Aalborg University, 2013)
Special Session ‐ Skatteministeriets kørselsafgifter for lastbiler